PREVALENSI ANAK BERKESULITAN BELAJAR DI SEKOLAH DASAR SE-KECAMATAN PAYAKUMBUH KABUPATEN LIMA PULUH KOTA - YULIA NOVA RINA (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstrak: This research was due to the fact that there were some problems found at elementary schools in Kecamatan Payakumbuh Kabupaten Lima Puluh Kota. From the preliminary observation at two elementary schools in Kecamatan Payakumbuh, it was found that every year, there were always a number of students who were not qualified to continue to the next grade. Unfortunately, the learning problems that the students had were yet identified by the homeroom teachers as well as the special need education teachers. As a result, the services done by teachers at schools were not directed to help those students yet. Based on those premilinary research findings, this research was done to find out the prevalence of students with learning disability in order to make the teachers services more directed. The result of research analysis showed that from 647 students, 151 of them (23,3%) were having the learning disability in reading, 295 of them (45,6%) were having the learning disability in writing, and 83 (12,8%) were having the learning disability in calcuting. Keywords; Prevalence, learning disability.